2007
DOI: 10.1002/bmc.825
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and quantitative analysis of polyeptides using a new gradient system based on an abrupt change in adsorption of polypeptide to the reversed‐phase column packing

Abstract: During a study of 100 microL aliquots of urocortin containing various acetonitrile contents, we hypothesized that a change in the acetonitrile content in the solution across a specific content of acetonitrile (critical threshold) causes an abrupt change in adsorption capacity to the column packing. Circular dichroism measurements suggest that the conformational change induced by acetonitrile in the solution causes the abrupt change in adsorption capacity, and this solvent-induced conformational change is rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The 100‐fold diluted plasma samples were digested by 8 μg/mL trypsin for 5 h at 37°C. The HC68 peptide fragment in the digested samples was detected and quantified by peptide adsorption‐controlled (PAC)‐LC/MS (Goda & Sudo, 2007, 2008), consisting of Shimadzu Nexera MP (Shimadzu, Kyoto, Japan) and a QTRAP 6500 mass spectrometer (AB Sciex LCC, Framingham, MA, USA). The analytical column was Inertsustain AQ‐C18 (100 × 4.6 mm i.d., 5 μm; GL Sciences, Tokyo, Japan) and the temperature of the column oven was 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…The 100‐fold diluted plasma samples were digested by 8 μg/mL trypsin for 5 h at 37°C. The HC68 peptide fragment in the digested samples was detected and quantified by peptide adsorption‐controlled (PAC)‐LC/MS (Goda & Sudo, 2007, 2008), consisting of Shimadzu Nexera MP (Shimadzu, Kyoto, Japan) and a QTRAP 6500 mass spectrometer (AB Sciex LCC, Framingham, MA, USA). The analytical column was Inertsustain AQ‐C18 (100 × 4.6 mm i.d., 5 μm; GL Sciences, Tokyo, Japan) and the temperature of the column oven was 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study (Goda and Sudo, 2007), we investigated the effects of the amount of acetonitrile in solutions containing urocortin (molecular weight 4696) on its adsorption to various materials using 100 μL of urocortin solution with varying acetonitrile content and a standard gradient system. Our initial results indicated that the peak area of urocortin retained on the column was dramatically changed by the acetonitrile content, despite loading the same concentration of urocortin onto the LC system.…”
Section: Introductionmentioning
confidence: 99%